Dynamic VRP in pharmaceutical distribution—a case study - Magalhães, José Miguel de; de Sousa, Jorge Pinho (Central European journal of operations research, 2006)
In recent years, the pharmaceutical sector has gone through deep changes, partially due to the ageing of the population and to the increasing of costs in health care services. With margins that are getting lower and lower, the drug distribution problem to pharmacies has become much more important, particularly in large metropolitan areas. As pharmacies demand shorter delivery times, vehicle routing and scheduling problems become harder for distributors. It is recognized that the traditional system based on fixed routes does not fulfil the expectations of pharmacies and may, in some cases, be quite inefficient for distributors. In this work, a case study has been carried out and a change of the traditional approach is proposed, by adopting a system of variable routes that are dynamically designed, based on orders that are constantly arriving along the day. A dynamic algorithm is therefore proposed, meant to be run several times a day. It has four phases: first, a clustering of the orders is performed; second, potential routes are constructed; third, a route is selected for operation; and finally, that route is subject to an improvement process. The selection of the next route to be launched may be postponed in order to take advantage of subsequent information. The algorithm has been tested in the case study, by simulating one week of operation, and by comparing the results with the plan produced by the traditional way. Keywords: Dynamic Vehicle Routing Problem; Dynamic Routing Planning; Heuristics; Pharmaceutical Distribution.